Experience of Dry Eye Patients With Anxiety and Depression: A Qualitative Study - Yu, Haozhe; Zeng, Weizhen; Xu, Minhui; Wu, Wenyu; Feng, Yun (Frontiers in Medicine, 2022)
Purpose: Anxiety and depression are important risk factors for dry eye disease (DED). The aims of this research are to identify the cause of anxiety and depression in DED patients and explore their strategies in coping with DED. Methods: This is a qualitative study based on semi-structured interviews, and the interviews records were analyzed through inductive thematic analysis. Participants were recruited from a large university affiliated hospital in the north of China, including 47 participants affected by depression and anxiety. Results: Analysis revealed the causes of anxiety and depression in DED patients could be divided into three major themes and nine subthemes: (1) From hospital: including difficulties in diagnosing and seeking medical advice, neglect or lack of attention from clinicians, low treatment satisfaction and complex comorbidities; (2) From daily life: including life satisfaction and well-being, changes in lifestyle pattern and changes in workstyle pattern; (3) From society: including burden of disease and reduction of social interaction. Most DED Patients with anxiety and depression were more likely to face the condition as well as receive treatments negatively, while the others tended to seek treatments unduly and blindly. Conclusions: This investigation offers new insights into the understanding difficulties in DED patients with anxiety and depression, and provides valuable guidance for supporting them to reduce depression and anxiety as well as improve prognosis.